Efeect of Sulphur, Bradyrhizobium Inoculation, Initial Moisture Content of Seed and Storage Container on the Germination Percentage of Groundnut Seed (Bangladesh Journal of Scientific and Industrial Research, 2007)
The study was aimed at determining the effect of sulphur and Bradyrhizobium fertilized seed at different initial moisture content of seed and storage container, to improving the germination percentage of groundnut seed. The germination test was carried out after storing the seed for five months. Results revealed that seeds obtained from 60kg S/ha. stored in polythene bags retained the germination percentage up to the standard level of ISTA for 5 months efficiently. Least initial moisture content of seed (7.25 %) produced from the above doses of fertilizer elements also played a vital role in keeping the quality of stored seed. Results in the respect of storage performance in terms of percentage of germination indicated that groundnut seed obtained from sulphur and Bradyrhizobium fertilizer elements during production and stored in polythene bag can retain better seed quality, provided seed were dried to a safe moisture level of 7.25 % to 8.46 %. Bangladesh J. Sci. Ind. Res. 42(2), 175-186, 2007